2012
DOI: 10.1111/ics.12010
|View full text |Cite
|
Sign up to set email alerts
|

Internet‐based lay person rating of facial photographs to assess effects of a cleansing product and a decent cosmetic foundation on the attractiveness of female faces

Abstract: It is well established that decorative cosmetics can enhance female facial attractiveness. In this study, we investigated the effects of a cleanser and a decent foundation on attractiveness of female faces. Comparative rating of a set of facial photographs by a group of lay persons revealed that the cleansing product was significantly reducing the attractiveness of the stimulus persons. Treatment with the foundation increased the attractiveness of the female faces clearly. The authors conclude that even unobtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Controlled studies have consistently found that female faces are perceived as more attractive when wearing makeup. Most of these studies have employed professional makeup artists to apply the makeup (Batres et al, 2018;Bielfeldt et al, 2013;Etcoff et al, 2011;Graham & Jouhar, 1981;Gu eguen & Jacob, 2011;Huguet et al, 2004;A.L. Jones & Kramer, 2016;Killian et al, 2018;Mulhern et al, 2003;Nash et al, 2006;Osborn, 1996;Ueno et al, 2014), while a handful have used stimulus images for which the target women applied their own makeup (Aguinaldo & Peissig, 2021;Cash et al, 1989;A.L.…”
mentioning
confidence: 99%
“…Controlled studies have consistently found that female faces are perceived as more attractive when wearing makeup. Most of these studies have employed professional makeup artists to apply the makeup (Batres et al, 2018;Bielfeldt et al, 2013;Etcoff et al, 2011;Graham & Jouhar, 1981;Gu eguen & Jacob, 2011;Huguet et al, 2004;A.L. Jones & Kramer, 2016;Killian et al, 2018;Mulhern et al, 2003;Nash et al, 2006;Osborn, 1996;Ueno et al, 2014), while a handful have used stimulus images for which the target women applied their own makeup (Aguinaldo & Peissig, 2021;Cash et al, 1989;A.L.…”
mentioning
confidence: 99%
“…Such characteristics might relate to a consumer perception that younger skin is brighter and more radiant with an internal glow, whereas aged skin is duller, shinier and glossier. Colour can be analysed by standardized image analysis algorithms and radiance and attractiveness rated from digital photography including wrinkles .…”
Section: Colour and Radiancementioning
confidence: 99%
“…From the colour-coded images, an overall inhomogeneity parameter can then be calculated. algorithms and radiance and attractiveness rated from digital photography including wrinkles [34,38].…”
Section: Figurementioning
confidence: 99%
“…One way that women commonly manipulate their attractiveness is through the use of cosmetics. Studies have found that female faces are rated as more attractive with makeup when compared to without makeup (e.g., [13][14][15][16][17][18]). Consequently, one would expect that attorneys and trial consultants would advise their female clients to wear cosmetics for trial given the positive effect of attractiveness on jury decisions.…”
Section: Introductionmentioning
confidence: 99%